The Evaluation of Directly Observed Treatment Short-Course (DOTS) Implementation for TB in Hospital X - Ayu Prameswari (Universitas Muhammadiyah Yogyakarta, 2018)
This research discusses about implementation of DOTS strategy in implementing TB services in health service units that organize TB control programs in Indonesia. DOTS is a TB treatment strategy with drug ingestion control. This program focuses on finding cases as early as possible and patient healing. This research uses qualitative methods, using in-depth interview techniques, observation, and document review. The total number of respondents in this study is 9 people. Results input: Human Resources is a lot of officers in the DOTS team who have not attended the training. Facilities and infrastucture are sufficient just does not yet have a specail ply TB patient. Policies, both hospitals and the government are good enough. Process: inadequate political commitment to which internal and external networks are running is not maximized, microscopic examination not yet optimal because many patients who do not perform the examination at the beginning of the diagnosis, in the treatment of many patients who did not perform sputum checks and radiological examination for evaluation of treatment progress, non-standard OAT management, and incomplete records. This ultimately affects the output component where the healing rate is low only reached 21,1% and conversion rate 32,7%. The conclusion is from the result that the implementation of DOTS strategy in PKU Muhammadiyah hospital Gamping Yogyakarta has not optimally.